Intravenous Iron-Induced Hypophosphatemia: An Emerging Syndrome - Glaspy, John A. (Adv Ther, 2021)
Some, but not all, intravenous iron formulations have been recognized to induce renal phosphate wasting syndrome. Most commonly this has been reported following treatment of iron deficiency anemia (IDA) with ferric carboxymaltose (FCM). A search of PubMed identified relevant randomized controlled trials (RCTs), and case studies evaluating hypophosphatemia (HPP) resulting from intravenous iron treatment. While more recent larger comparative RCTs have confirmed that the majority of patients receiving FCM, especially those with normal renal function, may experience severe HPP, complete documentation is hampered by inconsistent reporting of serum phosphate in such trials. Similarly, while case series and RCTs have documented the persistence of HPP for several weeks or even months, the lack of studies lasting beyond 5–6 weeks has constrained full understanding of the duration of effect. Clinical trials have established that the mechanism involves the bone/metabolic axis with the elevation of intact fibroblast growth factor 23 playing the central role. Reports continue to accumulate of the clinical consequences of severe HPP which are, most commonly, bone abnormalities following repetitive dosing. Case reports and studies, however, have also shown that symptomatic hypophosphatemia can occur after a single FCM dose. The frequency of such events remains unknown, in part due to lack of awareness of hypophosphatemia coupled with the fact that the most common acute symptoms of HPP (fatigue and weakness) are the same for IDA and for many of the chronic diseases that cause IDA. Changes to US and European prescribing information for FCM should raise awareness of the potential for HPP and need to monitor patients at risk for it.